Structural insights into decoding of mRNA by the ribosome - Ramakrishnan, Venki (Henry Stewart Talks, 2008)
tRNA: the central player in translation, Selectivity and transition state, Decoding: selection of the correct tRNA, The bacterial ribosome, Antibiotics change the fidelity of the ribosome, Selection of aa-tRNA by the ribosome, The atomic structure of the 30S subunit, Testing the decoding model, Minor groove recognition of base pairing geometry, Tautomers and base pairs, Streptomycin, Base pairing and fidelity
Archived at 2020/08/13